FAKTOR FAKTOR YANG MEMPENGARUHI PENYEMBUHAN LUKA PADA PASIEN DIABETES MELITUS TIPE 2 DI RS DR HAFIZ CIANJUR - Daryaman, Usan; Nur Amalia, Irma; Adly Rachmawati, Rency Divya; Fitri Rejeki, Yunita; Sulistiyawati, Arie (Sekolah Tinggi Ilmu Kesehatan Dharma husada, 2024)
Many factors affect the duration of wound healing including age, gender, nutrition, wound degree, blood sugar control, wound care, physical activity. Most people with diabetes mellitus experience wounds that are difficult to heal and some even end up in amputation cases. The purpose of this study was to determine the factors that can inhibit wound healing. This research method uses descriptive quantitative using a non-probability sampling technique research design. The population in this study were all patients in the Gardenia inpatient room who had wounds with a history of diabetes mellitus from January to April as many as 55 patients. Data collection methods using questionnaires and observation sheets that have been prepared by researchers in accordance with the objectives of the study, questionnaires and research observation sheets are prepared based on theoretical reviews. The results illustrate that the relationship between age and wound degree has a p value of 0.027. The relationship between gender and wound degree had a p value of 0.004. The relationship between nutrition and wound degree had a p value of 0.009. The relationship between blood sugar control and wound degree had a p value of 0.000. The relationship between wound care and wound degree had a p value of 0.000. The relationship between physical activity and wound degree had a p value of 0.000. It can be concluded that age, gender nutrition, blood sugar control, wound care management, physical activity with wound degree have a significant relationship in patients with diabetes mellitus.